Dual preparation of hydrophobic and hydrophilic BaWO4:Eu phosphors. (June 2016) - Cho, Young-Sik; Huh, Young-Duk
Graphical abstract: Highlights: Red-emitting BaWO4 :Eu phosphors were prepared in hexane-water bilayer system. The hydrophobic nanometer-sized BaWO4 :Eu phosphors were obtained in hexane. The hydrophilic micrometer-sized BaWO4 :Eu dendrites were obtained in water. Abstract: BaWO4 :Eu phosphors were prepared by performing a solvothermal reaction in a water–hexane bilayer system. A barium oleate (and europium oleate) complex was obtained in hexane via a phase transfer reaction involving Ba 2+ (and Eu 3+ ) ions in an aqueous solution of sodium oleate. The outer surfaces of the nanometer-sized BaWO4 :Eu phosphors were capped by the long alkyl chain of oleate; therefore, the hydrophobic nanometer-sized BaWO4 :Eu phosphors preferentially dissolved in the hexane layer. The micrometer-sized BaWO4 :Eu phosphors were obtained in the water layer. The BaWO4 :Eu phosphors prepared in hexane and water yielded sharp strong absorption and emission peaks at 464 and 615 nm, respectively, due to the 7 F0 → 5 D2 and the 5 D0 → 7 F2 transitions of the Eu 3+ ions. The BaWO4 :Eu phosphors are good candidate red-emitting phosphors for use in InGaN blue-emitting diodes, which have an emission wavelength of 465 nm.